What Factors do Learners Attribute to Their Speaking Achievement? - Toscu, Saliha (My University, 2020)
This study aims to explore the factors affecting speaking achievement of language learners who were studying at an English preparatory school at the university level in Turkey. The study involved the participation of 131 language learners who had intermediate level of English proficiency. The participants were chosen using convenience sampling and took part in the study on a voluntary basis. The instrument used to collect data basically had two parts. The first part involved Language Achievement Attribution Scale (LAAS) developed by Hsieh (2004), which aimed to reveal the reasons which the participants attributed to their speaking scores. The second part included Attitude/ Motivation Test Battery questionnaire (on a 5-point Likert scale) developed by Gardner (1985), which revealed the participants’ attitudes towards language learning, integrative and instrumental motivation, interest in foreign language and speaking anxiety. The data were analyzed on the Statistical Package for the Social Sciences (SPSS) and it was found that there was no statistically significant effect of motivation on language learners’ speaking achievement, but speaking anxiety influenced it. In addition, the study showed that there were differences among the participants in the reasons they attributed to their speaking success depending on how motivated and anxious they were.

Bu çalışma, Türkiye’de üniversite seviyesinde İngilizce hazırlık okulunda öğrenim gören öğrencilerin konuşma başarılarını etkileyen faktörleri ortaya çıkarmayı amaçlar. Çalışma, İngilizce yeterliği orta düzey olan 131 dil öğrencisinin katılımını içermektedir. Katılımcılar uygun örnekleme yöntemi kullanılarak seçilmistir ve çalışmada gönüllülük esasına bağlı olarak yer almışlardır. Veri toplamak için kullanılan araç temelde iki kısımdan oluşmaktadır. İlk kısım, katılımcıların konuşma puanlarına atfettikleri nedenleri ortaya çıkarmak için Hsieh (2004) tarafından geliştirilen Language Achievement Attribution Scale (LAAS) kullanımını içermiştir. İkinci kısım, katılımcıların dil öğrenmeye karşı tutumlarını, bütünleyici ve araç güdülenmesini, yabancı dile ilgilileri ve konuşma kaygılarını ortaya çıkaran Gardner (1985) tarafından gelitirilmiş Attitude/Motivation Test Battery anketi (5’li likert ölçeği üzerinde) kullanımını içermektedir. Veri Sosyal Bilimler İstatistik Programında (SPSS) analiz edilmiştir ve motivasyonun öğrencilerin konuşma başarısı üzerinde istatistiki önem tesiri olmadığı, fakat konuşma kaygısının konuşma başarısını etkilediği bulunmuştur. Ek olarak, çalışma katılımcılar arasında ne kadar motive ve kaygılı olduklarına bağlı olarak konuşma başarılarına atfettikleri nedenler bakımında farklar olduğunu göstermiştir.
What Factors Do Learners Attribute To Their Speaking Achievement?
Keywords: Attributions; Speaking Achievement; Motivation; Anxiety; Language Learning / Atıflar; Konuşma Başarısı; Motivasyon; Kaygı; Dil Öğrenme